Preparing Preservice Teachers Through Service-Learning: Collaborating with Community for Children and Youth of Immigrant Backgrounds - Lund, Darren E.; Bragg, Bronwyn; Kaipainen, Erin; Lee, Lianne (International Journal of Research on Service-Learning in Teacher Education, 2014)
This paper offers findings from a collaborative study that combined service-learning with a social-justice-themed university course that was an existing component of a teacher education program. First, the authors present a model for a community-led collaborative service-learning program in teacher education. Second, the paper explores the student learning outcomes emerging from this service-learning program. Drawing on existing literature from the fields of service-learning in teacher education and multicultural education, the authors suggest that this innovative, collaborative, community-led, service-learning program presents an effective model for better preparing preservice teachers for working with children and youth from immigrant backgrounds. The research findings emerge from a range of data sources including qualitative interviews with preservice teachers, field notes, and informal interviews and field observations with community partners. A key finding is that community-led efforts in service-learning can successfully realize the goals of teacher educators as well as those of the community partners.